Expression of Foxp3, CD25 and IL-2 in the B16F10 cancer cell line and melanoma is correlated with tumor growth in mice - Miranda Hernández, Diana Fabiola; Franco Molina, M.A.; Mendoza Gamboa, Edgar; Zapata Benavides, Pablo; Sierra Rivera, C.A.; Coronado Cerda, E.E.; Rosas Taraco, Adrián Geovanni; Taméz Guerra, R.S.; Rodríguez Padilla, María Cristina (Spandidos Publications, 2013)
The forkhead box P3 (Foxp3) transcription factor is one of the most studied markers used to identify CD4+CD25+ regulatory T cells (Tregs), and has been identified as a key regulator in the development and function of Tregs. Foxp3 expression has been reported in a variety of solid human tumors, including melanoma. The aims of the present study were to analyze Foxp3 expression in B16F10 melanoma cells in vitro, to determine whether this expression was affected during tumor growth in a murine melanoma model and to correlate Foxp3 expression with CD25 expression, interleukin (IL)-2 production and tumor weight. Foxp3 expression was analyzed with quantitative (q)PCR, flow cytometry and confocal microscopy. CD25 expression was analyzed by flow cytometry, and cytokine production was measured by ELISA [IL-2, interferon (IFN)-γ, transforming growth factor (TGF)-β and IL-10] and flow cytometry (IL-2, IFN-γ, IL-4 and IL-5). Foxp3 and CD25 expression was detected in the B16F10 cells in culture and in the intratumoral B16F10 cells. An increase in Foxp3 and CD25 expression was observed in a time-dependent manner during tumor growth at 7, 14 and 21 days. The production of the IL-2, IL-10, IFN-γ and TGF-β cytokines was observed in the B16F10 cells and also detected in the tumoral microenvironment during tumor growth (7, 14 and 21 days). An increase in IL-2 and IL-10 production was observed, whereas IFN-γ production decreased in a time-dependent manner. The production of tumor necrosis factor (TNF)-α was not observed in culture, but was detected during tumor growth, whereas the production of IL-4 and IL-5 was not detected. These data showed a positive correlation between the expression of Foxp3, CD25 and IL-2 and tumor weight in murine melanoma. From these data, it may be suggested that Foxp3 participates in melanoma growth, the modulation of the IL-2, IFN-γ and TNF-α cytokines and CD25 expression, and that it also plays a possible role in immunosuppression.